PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN KARAKTER RELIGIUS SISWA DI SMP IT TAZKIA INSANI - Minda Siti Solihah; Encu M Syamsul; Syafa’atun Nahriyah (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2023)
This study aims to (1) Determine the role of Islamic Religious Education teachers in SMP IT Tazkia Insani. (2) To determine the role of Islamic Religious Education teachers in improving the religious character of students at SMP IT Tazkia Insani. (3) To find out the efforts of Islamic Religious Education teachers in improving the religious character of students at SMP IT Tazkia Insani. This study uses descriptive qualitative research methods. Collecting data using several methods, namely interviews, observation and documentation. The results of this study are (1) The role of Islamic Religious Education Teachers at SMP IT Tazkia Insani in addition to having duties and roles as teachers, educators, supervisors, BPI coaches and as second parents for their students at school. The role of Islamic Religious Education Teachers in Improving the Religious Character of Students at SMP IT Tazkia Insani is carried out in the following ways: Educating students' character through historical methods; Using the Qur'an and Hadith as the main learning resources; Guiding students. (3) The efforts of Islamic Religious Education Teachers in Improving the Religious Character of Students at SMP IT Tazkia Insani are by way of Exemplary and providing examples directly, through the Mabit PAI exercise (Malam Bina Taqwa), Providing rewards and punishments.